Catecismos republicanos en España (1850-1874). Religión civil y propaganda democrática por preguntas y respuestas - Hernán Rodríguez Vargas (Cahiers de Civilisation Espagnole Contemporaine)
In Spain, between 1840 and 1848, were established political associations and democratic-republican promotion mechanisms, which over the following two decades consolidated the very political capacity to propose the formation of a Republic as an alternative to the monarchical model and, in the face of the pre-eminence of Catholicism, affirm the individual existence of a new republican civil religion. At the center of this dynamic are the republican catechisms, powerful communication tools, whose political language contributed to the formation of the most important concepts, codes and emblems of Spanish republicanism in the 19th century. The purpose of this article is to present, at first, the production and dissemination of republican catechisms in the dynamics of political promotion and socialization inscribed in the period between the 1854 revolution and the decline of the brief republican experience in 1874. In the second moment, it is proposed to analyze the content of the catechisms and answer the question about how, by placing the emphasis on the Republic, it was sought to establish a new civil religion, whose aim was the affirmation of important reforms of a democratic nature and whose eschatological end was "the salvation of the people", thus inverting the order of what had hitherto been the fundamental pillars of political life in Spain since the Ferdinand restoration in 1814, namely the alliance between the Monarchy and the Church.